Effect of plant growth regulators on sex expression, fruit setting, seed yield and quality in the parental lines for hybrid seed production in bitter gourd (Momordica charantia) - NAGAMANI, S; BASU, SUDIPTA; SINGH, SUKHBIR; LAL, S K; BEHERA, T K; CHAKRABARTY, S K; TALUKDAR, AKSHAY (The Indian Journal of Agricultural Sciences, 2015)
Effect of plant growth regulators on vegetative growth, sex expression,fruit setting, seed yield and quality was studied for hybrid seed production in the parental lines of bitter gourd (Momordica charantia L.) hybrids,Pusa hybrid 1 and Pusa hybrid 2 in rainy and spring-summer season. Plant growth regulators namely GA3 @ 50 ppm, NAA @ 200 ppm, maleic hydrazide @ 100 ppm, etherel @ 50 ppm were sprayed at three leaf and tendril initiation stage. The results showed that application of GA3 significantly enhanced vine length, number of branches and nodes/vine, fruiting, seed yield and quality in the parental lines in both the seasons.The plants sprayed with growth regulators showed induction of female flowers at lower nodes with 3-5 more pistillate flowers per vine and higher sex ratio as compared to unsprayed control. In manually pollinated flowers, plants sprayed with GA3@ 50 ppm had higher fruit and seed setting, fruit weight and hybrid seed yield. All the growth regulators had positive influence on vegetative, flowering and fruit traits in both the seasons but effect of growth regulators were more evident in rainy than springsummer season. GA3 @ 50 ppm, NAA @ 200 ppm, etherel @ 50 ppm were effective for enhancement in vegetative growth, fruit and seed yield and modification of sex expression but GA3 @ 50 ppm sprayed twice at three leaf and tendril initiation stage was most effective for hybrid seed production of bitter gourd.